Information systems in nephrology - Peličić Damir; Ratković Marina; Radunović Danilo; Prelević Vladimir; Bokan Darijo (Association of Nurses Technicians and Midwives, 2015)
The level of application of information technology in modern health systems is continuously growing throughout the world. Utilising new technology facilitates and speeds up the process of health care. The World Health Organisation has defined telemedicine 1997,, as the provision of health services in which distance represents a critical factor by health care professionals who use information and communication technologies for diagnosis, suggesting treatment and prevention of diseases, as well as the permanent training of health professionals in research and evaluation of health activities, in order to improve the health of people and the communities in which they live and work. Given,, tip of the iceberg ' which is now seen in terms of nephrology diseases in the future we can expect an increasing number of new information systems and technologies that will be applied in nephrology.